OBSERVATION OF SURFACE OPTICAL PHONONS ON SRTIO3(100) - Baden, A; Cox, P; Egdell, R; Orchard, A; Willmer, R (1981)
Surface optical phonons on the (110) face of tin (IV) oxide have been observed by high-resolution electron-energy-loss spectroscopy. Good agreement is found between experimental spectra and predictions based on a semi-classical theory, using the dielectric function from infra-red reflectivity data to evaluate the response of the crystal surface to scattered electrons. The problems of using energy loss spectroscopy to study adsorbates on surfaces of polar materials are considered in view of our observations. © 1983.